On the role of the AIS practitioner - Hart, Emma; Read, Mark; McEwan, Chris; Aickelin, Uwe; Greensmith, Julie (2013)
Cognisant of the gulf between engineers and immunologists that currenty hinders a truly inter-disciplinary approach to the field of Artificial Immune Systems (AIS), we propose a redefinition of the term AIS practitioner, as an individual who identifies those components and interactions captured in computational immunology models that are responsible for a particular property of interest (POI), and distils from these a set of algorithms and principles that can be applied in an engineering domain. We outline the role of the cross-disciplinary practitioner and the potential benefits to the field.